Feed efficiency with the addition of probiotics for asang fish fry, Osteochilus vittatus, CV - Usman Bulanin; Yuneidi Basri; Sri Puja Lestari (Depik, 2021)
The purpose of this study was to determine the addition of probiotics in commercial feed to the growth and survival of Asang fish (Osteochilus vittatus CV) fry. This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 3 replications. The test fish used were 120 fish with a size ranging from 5-8 cm. The test fish were kept in a waring cage made of a type of paralon frame with a size of 40 x 40 x 45 cm. The treatment in this study was A (without probiotics), treatment B (addition of probiotic 10 ml/kg of feed), treatment C (addition of probiotic 20 ml/kg of feed), and treatment D (addition of probiotics 30 ml/kg of feed). From the results of this study, the highest specific growth rate was found in treatment D (6.66 ± 1.15 g), while the mean survival was 100% for all treatments. The highest FCR of fish fry was found in treatment A namely 1.43 ± 0.22, and the lowest in treatment D namely 1.12 ± 0.21, and for feed efficiency in treatment D, namely 95.24 ± 1.04 %.Keywords:Asang fishEfficiencyGrowthSurvival